Developing The Speed and Accuracy of Strokes of Young Athletes Taekwondo WTF in Uzbekistan - Sh, Yusupova N. (International Journal of Psychosocial Rehabilitation, 2020)
This article describes methods for developing the speed and accuracy of young taekwondo WTF punches, the content of which is the systematic organization of rapid-force training tools and methods based on knowledge of the main types of punches used in taekwondo WTF, the mechanisms that determine the result and speed and accuracy in various types of defense and punches. is the specificity of the demonstration, the effectiveness of which is demonstrated in practice.